Desarrollo de políticas de seguridad informática e implementación de cuatro dominios en base a la norma 27002 para el área de hardware en la empresa uniplex systems s.a. en Guayaquil - Lamilla Rubio, Erick A. (2009)
The present project aims to design and implement informatics security policies based on the regulation 27002 for the company Uniplex S.A. which provide basic guidelines for information security, risk management and alternatives for their treatment. We will expose a risks treatment plan in which will identify appropriate actions as well as the responsibles for minimize the identified risks and then actually execute the implementation of the Project Management Information Security (PGSI) based on the selected controls and finally obtain as result the manual's procedures for the implementation of PGSI. For the system implementation will be based solely on the security's regulation for the information ISO-27002. For the realization it will create a summary that involves the steps to implement security in the company Uniplex Systems SA in Guayaquil. An audit will be conducted to determine the strengths and weaknesses of the company Uniplex Guayaquil on the security policies of informatics. Will be established procedures and processes of security that incorporate a series of measures over the Faculty information assets. Knowing, assuming and managing the possible risks in a way documented, structured and efficient which is adaptable to future changes.